Measurement performance quality of services (QoS) to optimizing on wireless sensor network topology for water pollution monitoring system. Issue 1 (July 2021) - Ghozali, M I; Sugiharto, W H; Susanto, H; Budihardjo, M A; Suryono, S
Abstract: The problem of the need for clean water is very important. The several diseases triggered by poor water quality reach more than 200 cases each year and cause more than 5 million deaths worldwide. Thus, monitoring water quality becomes important for the availability of safe and clean water. Wireless sensor networks have become a promising alternative to adopted for supplementing the conventional monitoring process. This network allows measurements from the remote location in real-time and with little human intervention. Wireless sensor network topology performance will support the stability of real-time data transmission. The difference in network topology between each router-node station affects the disruption of data distribution. Quality of Services (QoS) measurement is based on wireless sensor connectivity in transmit sensor data from several parameters, including temperature, total dissolved solids, and pH in the node station to the website service. The delay in transmitting data affects the performance of the measurement of the water pollution monitoring system.